Body fat, lipid profile and selected hormones in active male Polish students characterized by lower and higher normal thyroid-stimulating hormone levels - Malara Marzena; Widłak Patrycja (Biomedical Human Kinetics)
Study aim: To evaluate the relationship between body fat, lipid profile and selected hormones in the context of lower and higher normal thyroid-stimulating hormone (TSH) levels in active male students.